Seroprevalance of Theileria annulata in Elazig, Malatya and Tunceli provinces - Aktas, M; Sevgili, M; Dumanli, N; Karaer, Z; Çakmak, A (Tubitak Scientific & Technological Research Council Turkey, 2001)
This study was carried out to determine the seroprevalance of Theileria annulata in non-vaccinated cattle in Elazig, Malatya and Tunceli provinces between May 1997 and March 1998. Serum samples were collected from a total of 741 cattle in Elazig, Malatya, Tunceli and vicinities. Serum antibodies against T. annulata were investigated by the Indirect Fluorescence Antibody (IFA) test. In addition, peripheral blood smears were prepared and examined under the microscope. The seroprevalance of Theileria annulata in Elazig, Malatya and Tunceli provinces was 42.8%, 17.1% and 34.8%; piroplasm forms of Theileria annulata in these animals were 7%, 5.5% and 3%, respectively.
Keywords: Theileria annulata; IFA; cattle